Dobutamine Stress Echocardiography for Assessment of Systolic Function in Dogs with Experimentally Induced Mitral Regurgitation. (16th January 2014) - Suzuki, R.; Matsumoto, H.; Teshima, T.; Mochizuki, Y.; Koyama, H.
<x xml:space="preserve">Abstract</x> Background Systolic dysfunction is associated with poor outcomes in dogs with myxomatous mitral valve disease. However, assessment of systolic variables by conventional echocardiographic methods is difficult in these dogs because of mitral regurgitation (MR). Hypothesis We hypothesized that assessment of systolic function by dobutamine stress may identify systolic dysfunction in dogs with MR, and that 2‐dimensional speckle‐tracking echocardiography (2D‐STE) could quantitatively evaluate myocardial function. Animals Anesthetized dogs with experimentally induced MR. Methods Dogs were examined for systolic myocardial deformations using 2D‐STE during dobutamine infusion before and 3 and 6 months after MR induction. We evaluated peak systolic rotation and rotation rate in each basal and apical view; peak systolic torsion and torsion rate were also calculated. Results Invasive peak positive first derivatives of left ventricular pressure (dp/dt) were significantly decreased in dogs 6 months after induction of MR compared with pre‐MR results. After 3 and 6 months of MR, dogs had diminished peak systolic torsion values and torsion rates in response to dobutamine infusion compared with pre‐MR results (3 months, P < .001 and P = .006; 6 months, P = .003 and P = .021). These results were significantly correlated with overall invasive dp/dt (r = 0.644, P < .001; r = 0.696, P < .001). Conclusions and Clinical Importance Decreased torsion during dobutamine infusion in dogs with MR may reflect latent systolic dysfunction. Dobutamine infusion, therefore, may be useful for the assessment of systolic function in dogs with MR.